CITRA KAUM PEREMPUAN DI HINDIA BELANDA - Fika Hidayani; Isriani Hardini (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This article illustrates the position of Indonesian women in the Dutch colonial era, where women were treated arbitrarily, and they did not have the rights as human beings which equal to men. In fact, due to economic conditions and necessity, these women were willing to become a mistress and housekeeper in the Dutch household in Indonesia. This article is an interesting to discuss because the condition of women in Dutch colonial are rarely exposed to the media. A condition that was very dramatic that never happened again to women in Indonesia.